Longitudinal study to assess the quantitative use of fundus autofluorescence for monitoring disease progression in choroideremia - Dubis, AM; Lim, WS; Jolly, JK; Toms, M; MacLaren, RE; Webster, AR; Moosajee, M (MDPI, 2021)
Background: Characterisation of preserved autofluorescence (PAF) area in choroideremia (CHM) and its validity for monitoring disease progression in clinical trials is of importance.